NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN SURAT YUSUF - Ahmad Fuadi Romadhon (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: Values of character education is very urgent for knowed. It has been long recognized that self-governance itself depends upon the caracter of citizens. The nation founder repeatedly emphasized that national experiment would succed or fail depending upon the character education, we can not afford to implement it half-heartedly or wrong headedly. We need to take values of character education as seiously as we take academic education. Fortunately, highly demand to study values of character education in public school has openly accepted in many today’s societes that make it great issue for academicians to be investigated. However, most scholars carried out scientific research on many aspec values of character education program in holistic educational unit’s point of view or classroom based partially. In surah yusuf, there are many verses which are contains values of character education. Those values have same meaning with the eighteen values which is develoved by ministry of national education. The focus of this reseach is how the values of character education in surah yusuf. This study aims to determine the values of the character education contained in surah yusuf. This study is literature/ library, a research prosedure conducted by collection data or information through library materials such as alquran, hadith, books, paper, articles, magazinesPendidikan karakter merupakan hal yang sangat urgen yang perlu dipelajari. Telah lama dipahami bahwa kondisi sebuah pemerintahan ditentukan oleh karakter masyarakatnya. Berulangkali pencetus bangsa ini menekankan bahwa berhasil atau gagalnya suatu eksperimen negara akan ditentukan oleh nilai-nilai pendidikan karakter yang melekat pada kepribadian penduduk negeri itu. Penelitian ini merupakan penelitian literature/pustaka, yaitu prosedur penelitian yang dilakukan dengan mengumpulkan data atau keterangan melalui bahan-bahan pustaka seperti Alquran, Hadis, kitab-kitab tafsir, buku-buku, makalah, artikel, majalah ,jurnal, atau informasi lainnya yang mempunyai keterkaitan dengan kajian tema/judul yang dibahas. Data penelitian yang terkumpul, dideskripsikan secara mendetail kemudian dianalisis berdasarkan teori-teori pendidikan Islam dengan menggunakan contentanalysis (analisisisi), selanjutnya diinterpretasikan dalamsebuah kesimpulan. Hasil penelitian ini sesuai dengan pengelompokan ayat bahwa di dalam surat yusuf terdapat beberapa nilai pendidikan karakter sesuai dengan yang ditetapkan kemendiknas yaitu nilai religius, jujur, toleransi, kerja keras, rasa ingin tahu, semangat kebangsaan, menghargai prestasi,bersahabat/komunikatif, cinta damai, peduli sosial dan tanggung jawab.